Antioxidant potential of selected indigenous fruits using in vitro lipid peroxidation assay - Chua, Racquel Tan (Silliman Journal, 2010)
This study was primarily concerned in determining the antioxidant potential of the edible parts of selected indigenous fruits grown in the Cordillera region namely ayosep (Vaccinium angustifolium), bitungol (Flacourtia indica), kalamondin (Citrofortunella microcarpa), marble tomato (Lycopersicon pimpinellifolium), native lacatan (Musa paradisiaca), native passion fruit (Passiflora edulis), pinit (Rubus copelandii), rattan (Calamus mollis), tamarillo (Cyphomandra betacea) and tumok (Musa troglodytarum) as compared to Vitamin E. Antioxidant potential of the extracts was tested and measured using In Vitro Lipid Peroxidation Assay as indicated by absorbance value in mAU and % Lipid Peroxidation Inhibition. Based on this tests, all the fruits exhibited greater antioxidant potential than Vitamin E. NAtive passion fruit and rattan exhibited the greatest antioxidant potential and therefore, ranked 1.